Enhancing EFL Learners' Talk Through CL Facilitated TBL: Process - Asriyah, Siti (Department of English Language and Literature, Faculty of Languages and Arts, 2019)
This study aimed to explain how cooperative learning facilitates task-based learning in enhancing EFL learners? talk for eighth-grade students of SMPN 1 Magelang in the academic year 2018/2019. The researcher conducted the study based on Ellis (2003) and Kagan (1994) theories for explaining the process of teaching and learning activities using Task-Based Learning (TBL) and Cooperative Learning (CL) methods for enhancing EFL learners? talk. This study used a qualitative case study methodology. The instruments used were observation sheet, interview guidelines, and document analysis. Based on the data analysis, it can be concluded that cooperative learning techniques that facilitated the task-based learning in learning activities can enhance the EFL learners? self-confidence to talk in front of the class. Besides, task-based learning facilitated with cooperative learning techniques enhances students? courage and creativity, it also makes them more active. The practice also made them more understand the materials. There are some suggestions. First, it will become a good alternative for the teacher to look up some interesting materials for the students as their guidance to enhance their speaking habits. The students are suggested to be accustomed to learning to speak using group and pair techniques because the technique can motivate them to have a speaking habit. Lastly, the next researcher needs to conduct further research related to other techniques in helping the students to improve their talk. Keywords: Task-based Learning, Cooperative Learning, enhance, EFL learners? talk